Hysteria: Female's Sexuality History - Elena María Fernández Laveda; Águeda Fernández Martínez; Irene Belda Antón (Universidad de Alicante, 2014)
Introduction: Hysteria comes from hysteron, a Greek word that means Uterus. From there it follows the feminization of the disease and the link with the prototype of perfect woman at that time. Objective: Study the relationship between Hysteria and female sexuality through different historical periods. Materials and Methods: Literature Review in Databases. Results: Different studies try to explain the etiology and symptomatology of Hysteria. It calls our attention that some women were treated in a clandestinely way: pelvic massages. Conclusions: Analysis of the legacy of women who suffered from the stigmatization of being branded as hysterical women at present. How we see hysteria today: meaning and connotations.